Operational principles for fostering transformative qualities and capacities in higher education sustainability science and practice - Fagerholm, Nora; Coles, Neil; Beery, Thomas; Torralba, Mario; Hakkarainen, Viola; Albert, Christian; Andersson, Erik; Bergström, Ryan; Bieling, Claudia; Gentin, Sandra; Klonner, Carolin; Stahl Olafsson, Anton; et al. (Springer Nature, 2026)
Education for sustainability is widely recognised as a critical pathway for driving the transformations needed to address today’s polycrisis. Despite growing theoretical and conceptual advancements in sustainability education, current approaches have not achieved the deep systemic changes required. While university networks and individual institutions increasingly integrate sustainability into their education, concerns persist that transformative learning agendas often remain superficial. In particular, they frequently fail to equip learners with the emotional resilience and skills necessary to engage effectively with complex global challenges, as well as educators with the pedagogical framework to facilitate such learning. This article emphasises the need to advance transformative learning in sustainability science and practice in higher education by addressing the inner dimensions of sustainability: our individual and collective values, beliefs, worldviews, and associated transformative qualities and capacities. This means targeting deep leverage points and meaningful change by supporting more relational approaches, including an integrated inner–outer change in being, thinking, and acting. We provide seven operational principles for supporting the inner–outer transformation towards sustainability in learning and teaching sustainability science and practice, especially in geography and related fields. These principles highlight the importance of nurturing five clusters of transformative qualities and capacities—awareness, connection, insight, purpose, and agency—guided by relational approaches required to support profound and integrative learning experiences. We provide concrete examples of how to implement these principles. The proposed principles aim to inspire educators and learners to deeply engage with sustainability challenges to contribute to transformative change across individual, collective, and system levels.